Human Infections with Plasmodium knowlesi, the Philippines - Luchavez, J.; Curameng, P.; Espina, R.; Bell, D.; Chiodini, P.; Nolder, D.; Sutherland, C.; Lee, K.S; Singh, B. (Emerg Infect Dis., 2008)
Jennifer Luchavez, Fe Espino, Peter Curameng, Ronald Espina, David Bell, Peter Chiodini, Debbie Nolder, Colin Sutherland, Kim-Sung Lee, and Balbir Singh